Within-host acquisition of colistin-resistance of an NDM-producing Klebsiella quasipneumoniae subsp. similipneumoniae strain through the insertion sequence-903B-mediated inactivation of mgrB gene in a lung transplant child in China - Wu, Yongli; Zhao, Jiankang; Li, Ziyao; Liu, Xinmeng; Hu, Yanning; Zhang, Feilong; Zhang, Yulin; Pu, Danni; Li, Chen; Zhuo, Xianxia; Shi, Huihui; Lu, Binghuai (Frontiers in Cellular and Infection Microbiology, 2023)
Colistin is considered the "last resort" antibiotic for carbapenem-resistant Klebsiella.Yet, colistin-resistant Klebsiella strains have been emerging, and the underlying mechanism of this shift is still not fully understood. The insertional inactivation of the mgrB gene is an important colistin resistance mechanism in K. pneumoniae. However, K. quasipneumoniae subsp. similipneumoniae (KQSS), a novel Klebsiella subspecies, has been scarcely reported to be colistin-resistant. Herein, we reported an NDM-1producing KQSS strain KQ20605 recovered from a 7-year-old boy who developed resistance to colistin (KQ20786) by acquiring an IS903B element between the -27 th and -26 th bp of mgrB promoter region after 6-day colistin treatment. Through genome comparison between KQ20605 and KQ20786, the IS903B element was detected to integrate into the mgrB gene of KQ20786. It had a 100% nucleotide identity and coverage match with one IS903B on plasmid pKQ20605-IncR, and only 95.1% (1005/1057) identity and 100% coverage to those on the chromosome, indicating the role of plasmids as possible donors for IS903B-mediating colistin resistance. We also conducted in vitro colistin-induced experiments and observed, upon the pressure of colistin, KQ20605 could switch its phenotype from colistin-sensitive to resistant due to the insertions of IS elements (e.g., IS903B and IS26) into mgrB gene at "hotspots"; also, the insertion sites of IS903B were nearly identical to that of KQ20786 strain. Furthermore, IS26 elements in KQ20605 were only encoded by two plasmids, namely, pKQ20605-IncR and conjugative plasmid pKQ20605-IncN harboring blaNDM-1. In summary, this study provides clinical and experimental evidence that mobilizable IS elements on plasmids tend to be activated and integrated into the mgrB gene at "hotspots" in this KQSS, possibly causing the colistin resistance emergence and further dissemination.